A novel dual-emission fluorescent probe for the simultaneous detection of H2S and GSH. Issue 25 (7th March 2016) - Li, H.; Peng, W.; Feng, W.; Wang, Y.; Chen, G.; Wang, S.; Li, S.; Li, H.; Wang, K.; Zhang, J.
Abstract : A novel chlorinated coumarin–malononitrile fluorescent probe was synthesized for the simultaneous detection of H2 S and GSH from different emission channels. Abstract : A novel chlorinated coumarin–malononitrile fluorescent probe with three potential reaction sites, which exhibited highly selective, rapid response, low detection limit, and was capable of the simultaneous detection of H2 S ( λ ex/em = 515/564 nm) and GSH ( λ ex/em = 430/517 nm), was first proposed. The probe was successfully applied to dual-channel imaging H2 S and GSH in MCF-7 cells.